AKULTURASI BUDAYA LOKAL DAN AGAMA ISLAM DALAM MENYAMBUT RAMADHAN: Studi Kasus Tradisi Mersik di Kebon Daya, Masbagik Timur - HAMZANI, YUSRI (Al-Irfani: Journal of Al Qur'anic and Tafsir, 2020)
Kebon Daya community in East Masbagik Village has a unique tradition ofwelcoming Ramadhan. Tradition inherited through the ages named mersik whichmeans cleaning. This ritual consists of two stages of cleansing which are mersikzahir and mersik bathin. The first stage is specially for cleansing house of worshipand along the path to it. Meanwhile, mersik bathin is about sanctification of heartand spiritual. This reality is analyzed by examining the acculturative religiousexpression between religion (Qur’an verses and hadith) with cultural rules binding(customs and traditions). In the study of diversity, the scope of this discussion isincluded in the category of living Qur'an and living hadith that examine aspects ofreligious expression based on the Qur'an and hadith. Basically, the study of theliving Qur'an and living hadith are based on aspects of the validity of the text,interpretations of the text, and the extent to which the text influences theanthropological ritual patterns of the people affected by the text.